A Brief Introduction of Ex-Royal Nepal Army Doctors and Technical Medical Officer’s Society (ERNADTMOS) - Subedi, Nayan Bahadur (Medical Journal of Shree Birendra Hospital, 2001)
A Brief Introduction of Ex-Royal Nepal Army Doctors and Technical Medical Officer's Society (ERNADTMOS)